If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2x + 11) = 11 Reorder the terms: -4(11 + 2x) = 11 (11 * -4 + 2x * -4) = 11 (-44 + -8x) = 11 Solving -44 + -8x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '44' to each side of the equation. -44 + 44 + -8x = 11 + 44 Combine like terms: -44 + 44 = 0 0 + -8x = 11 + 44 -8x = 11 + 44 Combine like terms: 11 + 44 = 55 -8x = 55 Divide each side by '-8'. x = -6.875 Simplifying x = -6.875
| 2x+45=x-5 | | x^3+7x^2-9x=63 | | x^2+27x+6=0 | | y^2+18y+13=-4 | | -2(y+3)=2y+3 | | x/2+16=77 | | 2(4+4r)+3r=63 | | y^3-7y^2+10=0 | | c/2+16=77 | | 3d-24-5=9b+18+1 | | 2(4+4r)+3=63 | | 7n^2-14n+54=-5 | | 13+17y-3(y+11)= | | 5n+3=9 | | -7=-11+x/5 | | -t+2=10 | | 6y-9y=-16-20 | | 5b^2=-12 | | 55-40=30 | | -8x-2-9x-1=4 | | 14x+13-8x-1= | | 10=1x+2 | | (3x^2-3x-2)+(3x^2+4x-3)= | | 2(3-4k)=-51+3k | | 3(3x-2)-13=4x-4 | | 10+2x+2x+x=3000 | | 3+3+(2d-5)+(2d-5)=2+2+(2d-4)+(2d-4) | | 14-3x+7=76 | | x-2=x/5 | | 1000-2p=-100+10p | | 9x+12=3x-42 | | 70=2(6b+5) |